THE IMPORTANCE OF STUDY EXCURSIONS FOR SCHOOL STUDENTS (Intent Research Scientific Journal, 2023)
The role and importance of educational trips in imparting knowledge to schoolchildren and strengthening their acquired knowledge is shown in the article.